1990
DOI: 10.1097/00000658-199010000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Calcium, Parathormone, and Mortality in Critically 111 Surgical Patients

Abstract: A prospective study measured ionized calcium and parathormone sequentially at 48- to 72-hour intervals in 25 surgical intensive care unit patients. Twelve patients (48%) died at mean day 40 and median day 26. Levels of ionized calcium, parathormone, blood urea nitrogen, creatinine, albumin, magnesium, and phosphate for patients who lived were compared with levels for patients who died. The incidence of hypotension, renal failure (creatinine greater than or equal to 3.0), and bacteremia, as well as the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 31 publications
8
51
0
Order By: Relevance
“…It has been suggested that hypocalcemia in critically ill patients might be caused by the resistance to the action of PTH in the kidney and bone. There are many previous studies which are demonstrated elevation of PTH is associated with disease severity and mortality [23,[30][31][32]. Our results support previous studies.…”
Section: A) B)supporting
confidence: 92%
“…It has been suggested that hypocalcemia in critically ill patients might be caused by the resistance to the action of PTH in the kidney and bone. There are many previous studies which are demonstrated elevation of PTH is associated with disease severity and mortality [23,[30][31][32]. Our results support previous studies.…”
Section: A) B)supporting
confidence: 92%
“…It can lead to serious conditions [13,14]; it has been suggested that hypocalcemia is associated with the severity of disease and fairly predicts mortality in critically ill patients [15][16][17]19]. Hypocalcemia in critical illness is presumably multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the common causes of hypocalcemia ( PTH is one of the major regulators of extracellular calcium lying in a negative feedback way responding to changes in ionized calcium levels and vitamin D. PTH reportedly affects vascular smooth cells and ventricular myocytes [29], and impairs cardiac energy production, transfer, and utilization by enhanced entry and the accumulation of calcium in the myocardium [30] leading to development of cardiovascular disease [20,[31][32][33]. There have been several reports of elevated PTH value in patients with acute disease, which was associated with disease severity and poor outcome [17][18][19][20]. In most cases with acute illness, hypocalcemia was not restored by elevated concentration of PTH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations